A Heterostructure Metal Oxide Based Photoanode for Photoelectrocatalytic Degradation of Water Pollutants and Hydrogen Generation - Katie Davies (2022)
With a growing population the production of medication and cleaning products has increased significantly. This has resulted in these compounds entering freshwater sources as current wastewater treatment technologies are unable to completely remove them. This can cause harm to aquatic and human life while increasing bacteria’s resistance to disinfectants. Therefore, this study focused on utilising photoelectrocatalysis (PEC) to determine its feasibility as an alternative process for removing pollutants from water. In this study a WO3/BiVO4 photoanode was successfully synthesised which could produce a high photocurrent of 2.75 mA/cm2. Utilising this photoanode with the optimised PEC operating parameters determined in this study a high degradation of ibuprofen (96%), benzyldimethyldodecylammonium chloride (100%) and sodium 2-naphthalenesulfonate (100%) was achieved. This demonstrated how successful the PEC system developed in this study was in degrading pollutants that current water treatment technologies struggle to remove. However, there were some drawbacks identified with utilising PEC. In relation solely to the ibuprofen degradation process, 4-isobutylacetophenone was identified by the mass spectrometer as one of the main by-products. This is an environmental concern as this compound is more hazardous than ibuprofen. Significantly, however it highlighted the importance of utilising a mass spectrometer to identify by-products produced during pollutant degradation and determine the toxicity of the resulting solution. A further drawback identified was that during the degradation of all the pollutants the pH of the treated solution was very acidic (2.59-2.75) which means a post-treatment step is required to help neutralise the solution. However, this study did evidence a significant benefit of utilising PEC in that it can produce considerable amounts of hydrogen with or without pollutant degradation. PEC can be utilised to produce hydrogen in a sustainable way.